Improving exercise prescriptions for hematological cancer patients during and after allogeneic stem cell transplantation: conclusions from two large randomized controlled trials - Kühl, Rea (2016)
The evidence of exercise as adjuvant therapy option in cancer patients is increasing. Exercise constitutes a promising intervention to reduce treatment-related side-effects and to improve the rehabilitation process. Thus, there is growing interest in determining optimally targeted exercise prescriptions to maximize effects. However, few randomized controlled trials (RCTs) were conducted in haematological cancer patients during and after allogeneic stem cell transplantation (allo-HCT). Consequently, information regarding detailed exercise prescriptions and exercise response is lacking. Furthermore, a detailed description of adherence and related determinants would improve the understanding of exercise participation. The aim of this cumulative thesis is therefore to further close the indicated research gaps. Four manuscripts constitute the main body of this work. In these we (I) determined the individual training response dependent on physical performance level at baseline; we (II) described a large randomized controlled exercise intervention trial (PETRA study); we (III) compared recommended endurance exercise intensity classes to values obtained in haematological cancer patients; and we (IV) pictured adherence and its determinants in different treatment periods as well as the physical activity level of the control group within the PETRA study. Additionally, this thesis translates the findings into the current research context in the discussion part. The results will further refine exercise recommendations and exercise programs and will give important information for future study designs and data interpretation. (I) The first manuscript analysed data from 52 patients randomized to the experimental group in an RCT prior to, during and after allo-HCT. Results show that initially unfit patients had a significant better development of muscle strength and endurance performance during intervention period than the initially fit patients. For example, fit patients lost 31% of their knee extensor strength, whereas unfit patients lost only 1% (p=.03). For endurance capacity, the initially fit patients lost 4%, whereas the unfit patients gained 13% (p<.01). This finding is of major clinical relevance because exercise is often not recommended in deconditioned patients. (II) The second manuscript describes the PETRA study design. In this RCT, 256 patients prior to allogeneic stem cell transplantation will be included. The primary endpoint will be overall-survival after two years. Secondary endpoints include physical performance, fatigue, quality of life, severity of side-effects and biomarkers. Gold-standard assessment procedures to assess physical performance and physical activity will be applied. The experimental group performs a partly supervised one-year combined (endurance and resistance training) moderate-intensity exercise program, the control group receives a comparable intervention, but with progressive muscle relaxation. The PETRA study will provide a large database to investigate the multidimensional effects of exercise on various clinical outcomes. (III) In the third manuscript we compared for the first time commonly used endurance exercise intensity classes from the American College of Sports Medicine (ACSM) with cardiopulmonary exercise data obtained in a cancer population (106 patients prior to and 180 days after allo-HCT). The analysis revealed that the ACSM’s exercise intensity recommendations for endurance training might not meet the targeted intensity classes in almost all classes (p<.05). The use of ACSM’s intensity classes would result in over- or under-estimation of endurance exercise intensity in allo-HCT patients. In order to give appropriate exercise prescriptions and to compare intensities between other studies, we provided tables with exercise intensity classes obtained in haematological cancer patients. Furthermore, we revealed that applying exercise intensity recommendations based on percentages of the commonly used equation 220-age did not provide appropriate intensities, and is therefore, not recommended. We expect that our results will further improve exercise prescription in haematological cancer patients. (IV) The fourth manuscript examined exercise adherence and physical activity in the control group (contamination) including the first 153 patients of the PETRA study. With 66-77% (89–199 min/ week) adherence was acceptable in all three studied periods (inpatient, outpatient up to day 100, day 100 up to day 180). Most important determinants for adherence were fatigue (p=.004), physical performance (p=.003) and prior exercise engagement (p=.010) in different studied periods. The models could explain 16%, 21% and 55% of variance respectively. Exercise contamination in the control group was evident in 54% (89% were walking on a regular basis). Determinants for exercise contamination were higher muscle strength (p=.025) and less fatigue (p=.050). Total variance explained was 29%. The recruitment of the first 153 patients in the PETRA study was excellent (73%), providing us with a representative sample of this challenging population. The results give important implications for personalized exercise programs and future data interpretation. In conclusion, this cumulative thesis gives essential information regarding questions on how to individually tailor exercise interventions for haematological cancer patients. Furthermore, the identification of determinants of both, adherence to exercise intervention and contamination of the control group will improve exercise programs and illustrate the need to pay more attention on physical activities performed in the control groups.
Keywords: Hochschulschrift; Periphere Stammzellentransplantation; Chemotherapie; Körperliche Aktivität; Onkologie; Sport; Training